2016
DOI: 10.1016/j.neuroimage.2015.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Statistical estimation of T1 relaxation times using conventional magnetic resonance imaging

Abstract: Quantitative T1 maps estimate T1 relaxation times and can be used to assess diffusetissue abnormalities within normal-appearing tissue. T1 maps are popular for studying the progression and treatment of multiple sclerosis (MS). However, their inclusion in standard imaging protocols remains limited due to the additional scanning time and expert calibration required and susceptibility to bias and noise. Here, we propose a newmethod of estimating T1 maps using four conventional MR images, which are intensity-norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…While there are limitations to the development of biomarkers using the quantitative information of conventional MRI intensities, previous studies have shown that a great deal of quantitative information in the MRI intensities can be harnessed to study disease [Sweeney et al, 2016, Reich et al, 2015, Ghassemi et al, 2015b, Mejia et al, 2015, Meier et al, 2007]. The present results show that the development of biomarkers using MRI studies in many neurological and psychiatric disorders could benefit from the RAVEL scan-effect correction tool.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…While there are limitations to the development of biomarkers using the quantitative information of conventional MRI intensities, previous studies have shown that a great deal of quantitative information in the MRI intensities can be harnessed to study disease [Sweeney et al, 2016, Reich et al, 2015, Ghassemi et al, 2015b, Mejia et al, 2015, Meier et al, 2007]. The present results show that the development of biomarkers using MRI studies in many neurological and psychiatric disorders could benefit from the RAVEL scan-effect correction tool.…”
Section: Resultsmentioning
confidence: 66%
“…Shinohara et al [2014] used a NAWM stripe to estimate a scaling and shifting parameter in their z -score normalization method. In Mejia et al [2015], in the context of estimating quantitative T 1 maps ( qT 1 ) from conventional MRI, the authors proposed an adaptation of the z -score normalization method by using a combination of NAWM and cerebellar gray matter (CBGM), where the NAWM was used for the scaling parameter and the CBGM was used for the shifting parameter. In Ghassemi et al [2015b], the authors used the median GM intensity for the shifting parameter, and the difference between the median intraconal orbital fat intensity and the median GM intensity for the scaling parameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MCPHEE and WILMAN Researchers have sought to acquire quantitative maps rapidly by either directly fitting standard weighted images [12][13][14] or through use of specialized or nonstandard sequences (e.g., fingerprinting, 15,16 DESPOT1 and DESPOT2, 17,18 QRAPMASTER, 19,20 or multislice inversion recovery 21 ). In some cases, dictionary methods are used for parameter quantification.…”
mentioning
confidence: 99%
“…However, recent advances in neuroimaging analysis have emphasized multimodal techniques in order to include covariance modeling across modalities [11] [12] [13]. This relationship, which we refer to as coupling or inter-modal coupling (IMCo), is known to differ across tissue types [14] [15]. However, it is unknown whether IMCo is disrupted in pathological conditions such as MS. We propose to leverage IMCo information as features for lesion segmentation in order to quantify the coherent changes as tissue damage and repair occur across imaging modalities.…”
Section: Mimosa and Imco Regressionmentioning
confidence: 99%